Election promises: Why social schemes like NYAY need to be well thought out - Pradhan, Mamata; Roy, Devesh (Indian Express Group, 2019)
The build-up to the 2019 elections inter alia has been characterised by competitive claims of formulae and formula to address poverty with rallying cries of surgical strikes, final assaults and “it is achievable”. In these schemes of things, cash handouts seem to be of essence in the election season. In the market for disadvantage (demand for recognition and supply of solutions), social protection programmes play an important role. Social protection schemes are meant to mitigate the immediate impact of shocks (for example, price fluctuations) and smoothen consumption, over time. The thinking has also evolved to emphasise graduation and self-reliance where households are enabled to meet their needs consistently.